Hubungan Komunikasi Interpersonal Pelatih dengan Motivasi Pemain - Enjis Argi Prayugi Prisswigstya; Rakhmaditya Dewi Noorizki (Flourishing Journal, 2023)
Coach interpersonal communication is an important factor in player motivation. The role of the coach is not only to train the performance of the players but also to be able to communicate well so that they can become an external driver for the players. The purpose of this research is to determine the relationship between coach communication and player motivation. This research uses a literature review research design. There are five journals with a minimum publication year of 2018. The results of the data analysis show that there is a significant relationship between coach interpersonal communication and player motivation. The subjects studied were table tennis athletes, badminton women's doubles athletes, club woodball players, futsal athletes, and UKM athletes. Good interpersonal communication gives players the opportunity to increase their motivation when competing. Apart from that, based on the results of intervention in the form of effective communication training, it also shows a significant influence on player success. Effective communication can increase the sense of trust between players and coaches so that it can improve player performance. AbstrakKomunikasi interpersonal pelatih menjadi faktor penting dalam motivasi pemain. Peran pelatih tidak hanya melatih performa pemain tetapi harus mampu berkomunikasi dengan baik sehingga mampu menjadi salah satu pendorong eksternal bagi pemain. Tujuan penelitian ini untuk mengetahui adanya hubungan komunikasi pelatih dengan motivasi pemain. Penelitian ini menggunakan desain penelitian tinjauan pustaka. Terdapat lima jurnal dengan minimal pernerbitan tahun 2018. Hasil analisis data menunjukkan apabila ada hubungan yang signifikan antara komunikasi interpersonal pelatih dan motivasi pemain. Subjek yang dikaji yaitu atlet tenis meja, atlet ganda putri bulutangkis, pemain club woodball, atlet futsal, dan atlet UKM. Komunikasi interpersonal yang baik memberi peluang pemain untuk meningkatkan motivasi mereka saat bertanding. Selain itu berdasarkan hasil intervensi berupa pelatihan komunikasi efektif juga menunjukan pengaruh yang signifikan pada keberhasilan pemain. Komunikasi efektif dapat meningkatkan rasa percaya antara pemain dan pelatih sehingga mampu meningkatkan performa pemain.